2017
DOI: 10.1186/s40557-017-0187-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between serum vitamin D levels and sleep quality in fixed day indoor field workers in the electronics manufacturing industry in Korea

Abstract: BackgroundAlthough recent studies have investigated the influence of vitamin D on sleep patterns, there is a lack of research on the relationship between vitamin D and sleep patterns in Korean workers. This study focused on the relationship between serum vitamin D levels and sleep in fixed day indoor field workers in the electronics manufacturing industry in Korea.MethodsThe 1472 subjects who were included in this study were selected from fixed day workers in the electronics manufacturing industry who had rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 46 publications
0
24
1
1
Order By: Relevance
“…Kim et al [22] reported a positive relationship between serum 25(OH)D concentrations and sleep duration, whereas Shiu [23] found no significant association. In contrast to our results, Jung et al demonstrated a correlation between 25(OH)D levels and sleep quality using PSQI [26]. While Beydoun et al [25] reported an inverse relationship between serum 25(OH)D concentration and sleepiness (i.e.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Kim et al [22] reported a positive relationship between serum 25(OH)D concentrations and sleep duration, whereas Shiu [23] found no significant association. In contrast to our results, Jung et al demonstrated a correlation between 25(OH)D levels and sleep quality using PSQI [26]. While Beydoun et al [25] reported an inverse relationship between serum 25(OH)D concentration and sleepiness (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…However, only a marginal negative association was reported between serum 25(OH)D concentrations and very short sleep, when a sub-group with very short sleep duration (<5 hours per night) was compared to a sub-group with normal sleep duration (7–8 hours per night). Among Korean workers an odds ratio of 1.43 for having poor sleep quality (PSQI (Pittsburgh Sleep Quality Index) score<5) was found in case of vitamin D deficiency (<10 ng/mL) [26].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, 9 studies were included in our meta-analysis. The detailed study selection is described in Figure 1 [ 20 , 26 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were mixed gender, two included only women [ 26 , 33 ], and one was only male [ 20 ]. For vitamin D deficiency cut-off value, the included studies mainly used 20 ng/mL [ 20 , 26 , 31 , 33 , 35 ] in accordance with the criteria suggested by Institute of Medicine (IOM) [ 38 ]; three studies used 30 ng/mL [ 32 , 34 , 37 ], and only one study used 10 ng/mL [ 36 ] as the cut-off value. Seven of the nine studies adjusted for potential confounding factors, whereas other studies provided only crude-effect estimates.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with sleep disturbance showed lower levels of 25(OH)D as compared to those without sleep disturbance. Jung et al (23) investigated serum vitamin D levels in fixed day indoor workers in the manufacturing industry and analyzed the relationship of vitamin D deficiency with sleep quality. A significant correlation was observed between serum vitamin D deficiency and poor sleep quality.…”
Section: Discussionmentioning
confidence: 99%